THE CAUSALITY BETWEEN AGRICULTURAL RAW MATERIALS AND ECONOMIC POLICY UNCERTAINTY: EVIDENCE FROM THE TIME- VARYING GRANGER CAUSALITY - Tunc, Ahmet; Savas, Savas; Barak, Doğan (My University, 2023)
This paper aims to examine the time-varying dynamics of the causal interaction between agricultural raw materials commodity prices and the US economic policy uncertainty (EPU). To this end, we use monthly data for the period spanning from January 1992 to November 2021. We employ a time-varying Granger causality test to provide empirical evidence on the time-varying dynamics of the causality interaction and thereby revealing potential heterogeneities of these interactions during major historical events. The results show that causality running from EPU to agricultural raw materials, as well as causality running from agricultural raw materials to EPU, exhibits time-varying dynamics. More specifically, the findings reveal that causality generally tended to run from agricultural raw materials to EPU for most of the 2000-2014 period but reversed with the US-China trade war and the Covid-19 pandemic period. This result highlights the importance of modeling the potential causality interactions in the economic uncertainty-commodity prices nexus within a dynamic framework and implies that these interactions cannot be considered independently of the prevailing economic, political and global conditions.
Keywords: Tarımsal Ekonomi ve Politika; İktisat